A method and approach for evaluating coparenting events during couples group interventions - McHale, James P.; Irace, Karina; Cowan, Philip; Cowan, Carolyn Pape; Odgaard, Eric (Frontiers in Psychology, 2024)
When interventionists stimulate productive father-mother dialogues around coparenting, there are numerous potential benefits for families. Families stand to benefit from more positive involvement of fathers with both coparents and children, key contributors to healthy child developmental outcomes. In this report, we introduce a new strategy and rating system for helping practitioners and supervisors assess the nature and quality of coparenting-related dialogues and conversations in the context of couples group interventions. The system derives from analysis of 24 relationshipenhancement groups, 13 enrolling English-speaking couples and 11 enrolling Spanish-speaking couples, all parents of young children. All groups were co-led by a male-female team explicitly trained to focus on marital and parenting themes and supervised to address couples issues -not coparenting issues explicitly. All co-leaders spoke the native language of group participants. We documented how frequently coparenting events occurred, and how the nature and quality of events varied within and across groups. Overall, in both English-and Spanish-speaking groups expressly assembled to focus on marital and parenting issues, coparenting events occurred relatively infrequently. At the same time, both mothers and fathers appeared motivated to raise and discuss issues associated with their coparenting, and extended discussions about coparenting issues broached by the parents blossomed in approximately 37% of all instances. Process-oriented (rather than didactic) co-leader responses appeared especially helpful in scaffolding prolonged coparenting discussions. We propose that use of the system as a training, supervision and selfassessment tool can help clinicians become more consciously aware of how well their interventions succeed in promoting and scaffolding coparenting conversations during group interactions.